Presence Factor Scale (PFS): a Method for Assessing Presence in Immersive Virtual Environments - Souza, Vinicius C.; Nedel, Luciana P. (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais Estendidos do XXIV Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2022.227428, 2022)
The effectiveness of a Virtual Reality (VR) experience is strongly affected by the sense of presence of the users involved. The methods already proposed to measure presence rely on user experiments specifically designed. Regardless of the effectiveness of such studies, carrying out user evaluation is extremely costly since it requires expert planning, adequate volunteer recruitment, compliance with ethical standards, long application periods, and statistical analysis of the results. As an alternative, this work presents a lower cost, faster and highly applicable presence evaluation method, the Presence Factor Scale (PFS), which eliminates the need for user evaluations and can be used as a set of guidelines in the design of new VR experiences.